The Use of Customer Metrics in B2B Customer Retention - Vanhanen, Oona (fi=Turun yliopisto|en=University of Turku|, 2017)
B2B marketing has deep roots in relationship marketing where the relationship management, including the retention of existing customers, is considered important. Typically, it has been viewed that B2B marketing does not have wide access to customer data but following the explosive growth of data and technological advancements, that is not the case anymore. There is a gap in understanding the concept of customer retention in this data-driven era. Therefore, the purpose of this research is to describe how B2B companies use customer metrics to enhance customer retention. This is aimed to be answered through the following research questions: (1) How is customer retention understood and defined? (2) What customer metrics are used to measure customer retention? (3) How are customer metrics used to guide those marketing and sales activities that are executed to enhance customer retention? and (4) What barriers and enablers are identified to use metrics in guiding retention activities? The theoretical approach first defines customer retention and describes its importance. Subsequently, customer metrics are described and classified, which is followed by the description of marketing activities that aim to enhance retention. It is then suggested how metrics may guide the activities and what common barriers and enablers there exists to the use of metrics. This study was conducted as a qualitative single-case study to gain an in-depth and context specific description of the research phenomenon. The primary research data consisted of thematic semi-structured interviews and as secondary data there were documents and observations by the researcher. The findings suggest that customer retention is a concept that has different definitions based on the practitioner. However, three main dimensions, attitude, behavior and time, can be found. Even so, the hazy definition leads to an unclear understanding of what is the purpose of retention and which activities are executed to enhance it – and lastly, how customer metrics may be used to guide these activities. It was acknowledged that customer centricity and top management support enables the use of customer metrics but several barriers were also identified, such as cross-functional siloes, limited data availability and poor linkage to organizational processes. This study offers several conclusions through both theoretical contributions and managerial implications. It suggests that customer retention theory should focus on building a holistic view of customer retention, including how metrics are indeed used in a practical context. Also, managers can understand how metrics can be linked to retention and thus through customer analytics increase the focus of ROI (return-on-investment) for retention activities and bring value to the customer.